Acoustic and morphological identification of the sympatric cricket frogs Acris crepitans and A. gryllus and the disappearance of A. gryllus near the edge of its range - Micancin, Jonathan P.; Mette, Jeff T. (Zootaxa, 2009)
Although the Northern Cricket Frog, Acris crepitans, and Blanchard’s Cricket Frog, A. c blanchardi or A. blanchardi, have declined in areas near the northern margins of their ranges in the eastern and central United States, no such declines have been reported for the Southern Cricket Frog, A. gryllus, at the northern margin of its range in the Southeast. However, the status of A. gryllus is obscured by its sympatry with A. crepitans and the difficulty of identifying the two species. To address these difficulties, we studied A. crepitans and A. gryllus from North Carolina in the field and in a large museum collection. We quantified distinct differences in the click components of the vocalizations of A. crepitans and A. gryllus and used these differences to identify calling males from field recordings. Based on field recording and collection, we developed a discriminant function to identify preserved specimens by the extent of hind-foot webbing and the diameter of anal tubercles. During surveys from 2004 to 2007, we found that Acris crepitans was more widespread than expected from published reports, as it was frequently found in the Coastal Plain. Acris gryllus was less widespread than expected, as we could not find it in the northern part of the upper Coastal Plain, where published reports indicated it should occur. By applying our discriminant function to Acris collected in 1962 and 1963, we confirmed that A. gryllus once occurred in this area. In 2008, we resurveyed sites where A. gryllus had once occurred alone or in syntopy with A. crepitans and confirmed that A. gryllus is now missing from three major river basins in the upper Coastal Plain of North Carolina. We conclude that while the range of A. crepitans is stable in North Carolina, A. gryllus has disappeared from a large area near the northern edge of its range.